2002
DOI: 10.1055/s-2002-25727
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Growth, Secondary Metabolism, and Resistance of Apple

Abstract: The paper shows that N‐induced vigorous shoot growth increases susceptibility of apple trees to Venturia inaequalis. This is due to a weakened defence in infected leaves of the high N cultures showing large lesions with excessive sporulation, whereas infected leaves from the low N cultures exhibited successful defence with only small chlorotic lesions and no sporulation. This might be explained by biosynthesis of phenylpropanoids in the young leaves of the resistant trees. A negative correlation between shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 15 publications
4
44
0
Order By: Relevance
“…In contrast, the susceptible cultivar Golden Delicious expressed a thaumatin-like clone upon V. inaequalis infection which goes in line with the results on the protein level observed by Gau et al (2004). In addition, the pathogen-induced up-regulation of a F3'5'H gene which is assumed to be responsible for 3 0 -hydroxylation of flavonoids in Golden Delicious fits in the accumulation of catechins often observed in infected apple leaves (Mayr et al 1997;Leser and Treutter 2005;Treutter and Feucht 1990;Picinelli et al 1995;Rühmann et al 2002). These results give new insights into the response of apples, which are resistant or susceptible to the scab fungus and may help to understand mechanisms of basal defence and cultivar-specific resistance.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, the susceptible cultivar Golden Delicious expressed a thaumatin-like clone upon V. inaequalis infection which goes in line with the results on the protein level observed by Gau et al (2004). In addition, the pathogen-induced up-regulation of a F3'5'H gene which is assumed to be responsible for 3 0 -hydroxylation of flavonoids in Golden Delicious fits in the accumulation of catechins often observed in infected apple leaves (Mayr et al 1997;Leser and Treutter 2005;Treutter and Feucht 1990;Picinelli et al 1995;Rühmann et al 2002). These results give new insights into the response of apples, which are resistant or susceptible to the scab fungus and may help to understand mechanisms of basal defence and cultivar-specific resistance.…”
Section: Discussionsupporting
confidence: 78%
“…It was further shown that the inhibition of the enzyme phenylalanine-ammonia-lyase led to severe scab symptoms on the leaves of a resistant cultivar (Mayr et al 1997). Environmental conditions (N-fertilisation) favouring the growth of apple trees inhibited their flavonoid biosynthesis and increased the susceptibility to pathogen (Rühmann et al 2002;Rühmann and Treutter 2003;Leser and Treutter 2005). A transient inhibition of the flavanone 3-hydroxylase (FHT) in apple leaves by a treatment with the dioxygenase inhibitor Prohexadione-Ca r induced several changes in their flavonoid composition.…”
Section: Defensive Role Of Flavonoids In Applementioning
confidence: 99%
“…For this reason, the development of scab-resistant varieties appears as the best means of control. It is known that many plants species are resistant to certain diseases naturally (Rühmann et al, 2002). The resistance genes of resistant apple genotypes possibly act as regulatory genes of phenol synthesis (Michalek et al, 1999).…”
Section: Introductionmentioning
confidence: 99%